Reading Comprehension in L2: Effect of Explicit Instruction of Cognitive and Metacognitive Learning Strategies (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Explicit language learning strategy-based instruction has emerged as an advantage in teaching languages. Several studies have addressed this topic in Chile, focusing on the type of strategies used in university contexts. Thus, it is necessary to guide such inquiries to school levels. For this reason, the present investigation aims to study the impact that explicit instruction of cognitive and metacognitive learning strategies has on a group of Chilean high school students’ reading skills in L2. To achieve this, the study comprised two experimental groups and one control group. In the view of the results, it follows that cognitive strategies were more effective, and the explicit instruction of learning strategies constitutes a tool that favors the process of reading in L2.
Keywords: Language learning strategies; reading in L2; explicit instruction of language learning strategies; L2 learning